Робочі процеси інноваційних гідростатичних та аеростатичних сферичних шарнірів із струменевим регулюванням положення сфери - Струтинський, Сергій Васильович (НТУ "ХПІ", 2016)
Розглянуто робочі процеси пов’язані з течією рідини в проточних частинах інноваційних гідростатичних та аеростатичних сферичних шарнірів із струменевим регулюванням положення сфери. Обґрунтовано принципи і схемну реалізацію струменевого регулювання. Проведено розрахунки на ЕОМ поля течії в щілині та в системі керуючих струменів. Розроблено спеціальну методику аналітичного розрахунку параметрів течії в щілині шарніра на основі методу ламінарної аналогії. Сформульовані пропозиції по застосуванню раціональних методів технології машинобудування та прогресивних матеріалів у розроблених інноваційних конструкціях шарнірів.

The workflows associated with the flow of fluid in the flow area of innovative hydrostatic and aerostatic spherical hinges with adjustable jet provision sector are considered. The principles and circuit implementation of jet regulation were substantiated. The computer calculations of the flow field in the cleft and control system jets were done. A special technique of analytical calculation of parameters of flow in the cleft of the hinge on the basis of laminar analogy was developed. The series of prototypes with adjustable spherical joints were developed and tested. The variants of hydrostatic centering hinges and hinge areas of the vacuum centering and magnetic fields were designed in particular. The proposals on the application of rational methods of manufacturing engineering and advanced materials in the developed innovative hinges designs were formulated.
Workflows and innovative hydrostatic aerostatic spherical joints with adjusting the scope of the provisions of jet
Keywords: щілина; течія; розрахунок; дослідні зразки; flow; calculation; samples